Pengaruh Budaya, Kelompok Referensi, Dan Psikologis Konsumen Terhadap Orientasi Belanja Daring - Indra Maulana (LPPM UNIBI, 2020)
This study aims to determine the influence of culture, reference groups, and consumer psychology on online shopping orientation. This quantitative research was conducted on internet users in Purwakarta Regency, West Java Province. The research was conducted from February 2020 to September 2020. The sample was taken in a purposive manner with incidental sampling. The final number of respondents who participated in this study were 100 respondents. Linear regression analysis is used to determine the relationship model between X1, X2, X3, with the Y variable. The results of the analysis show that the three independent variables partially have a positive influence on Online Shopping Orientation in Purwakarta Regency. It can be concluded that the stronger the three independent variables are, the higher the influence in the formation of Online Shopping Orientation in Purwakarta.